Relationships Among Measures of Strength and Power and Health Outcomes in Youth - Lloyd, Adrian Douglas (East Carolina University, 2014)
The interest in musculoskeletal fitness and its overall impact on health has been increasing in the last decade. The Institute of Medicine (2012) report called for the addition of several muscular fitness tests to national surveys of youth health-related physical fitness and to fitness test batteries in schools and other educational settings. Purpose: The purpose of this study was to examine the relationships among various muscular fitness tests and health outcomes in youth. Methods: Participants included 49 boys and girls aged 9 to 14 years. A series of muscular fitness tests and tests of health outcomes were completed in two test sessions. Muscular fitness tests included the standing long jump, vertical jump, upper body power throw, total body power throw, and handgrip strength. Handgrip strength was expressed in absolute terms and allometrically scaled to a power of 0.67. The health outcomes examined were aerobic capacity, body composition, systolic blood pressure (SBP), diastolic blood pressure (DBP), and physical activity. Aerobic capacity (VO₂[subscript]max) was directly measured during a maximal treadmill test. Body composition (percent fat) was assessed with the BODPOD. Blood pressure was measured via auscultation after 5 minutes of seated rest. Physical activity was quantified as minutes of moderate-to-vigorous physical activity (MVPA) from 7-day accelerometer measurement. Bivariate correlations were calculated to examine the relationships among fitness tests of strength and power and health outcomes. To control for the impact of body mass index (BMI) and age, partial correlations were calculated among fitness tests and health outcomes controlling for BMI z-score and age. To examine relationships among fitness tests and health outcomes from a criterion-referenced perspective, participants were categorized into both the aerobic capacity and body composition Healthy Fitness Zone (HFZ) and Needs Improvement Zone (NIZ) as defined by FitnessGram®. Effect size (ES) estimates were calculated with Cohen's delta to examine the size of the difference between the HFZ and NIZ groups on the fitness test variables. Results: SBP and VO₂[subscript]max were moderately correlated with several fitness tests, including total body power throw (r = .37, -.28), upper body power throw (r = .33, -.31), and dominant (r = .44, -.33) and nondominant handgrip strength (r = .37, -.34). Percent fat was moderately correlated with the standing long jump (r = -.45) and vertical jump (r = -.50). The correlation between percent fat and handgrip strength was close to zero when handgrip strength was expressed in absolute terms. Moderate correlations were found between percent fat and handgrip strength when handgrip strength was allometrically scaled for body mass (r = -.50 and -.48). When partial correlations controlling for BMI z-score and age were calculated, generally a similar pattern of correlations was found, except that the partial correlations among SBP and the throwing tests and absolute handgrip strength were lower than the bivariate correlations. When the HFZ was defined with aerobic capacity standards, the HFZ group did better on the standing long jump than the NIZ group (ES = 0.45). However, medium effect sizes demonstrated that the NIZ group did better than the HFZ group on total body power throw (ES = -0.42), upper body power throw (ES = -0.59), and absolute handgrip strength (ES = -0.48, -0.39). Differences in the vertical jump and allometrically scaled handgrip strength favored the HFZ group over the NIZ group, but these differences were generally small (range of ES = 0.16 to .32). When the HFZ was defined with body composition standards, effect size estimates revealed large differences between the HFZ and NIZ groups favoring the HFZ group for standing long jump (ES = 0.84), vertical jump (ES = 1.06), and allometrically scaled handgrip strength (ES = 1.30, 1.42). Small to medium effect sizes were found for total body power throw (ES = 0.26), upper body power throw (ES = 0.19), and absolute handgrip strength (ES = 0.36, 0.43) favoring the HFZ group over the NIZ group. Conclusion: Results demonstrated moderate levels of norm-referenced and criterion-referenced evidence that the tests of musculoskeletal fitness used in the current study are health-related. However, findings also indicated that the significant relationships between these musculoskeletal fitness tests and health outcomes are highly influenced by body composition.
Keywords: Physical education; Fitness; Health; Outcomes; Power; Test; Youth; Musculoskeletal system; Muscle strength--Testing; Physical fitness for youth